2021
DOI: 10.1186/s40479-021-00160-y
|View full text |Cite
|
Sign up to set email alerts
|

Schema modes and their associations with emotion regulation, mindfulness, and self-compassion among patients with personality disorders

Abstract: Background The current study's goal was to examine the multivariate patterns of associations between schema modes and emotion regulation mechanisms in personality disorders. Schema modes are either integrated or dissociative states of mind, including intense emotional states, efforts to regulate emotions, or self-reflective evaluative thought processes. Exploring the multivariate patterns of a shared relationship between schema modes and emotion regulation strategies may lead to a better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Answers are rated on a 6-point Likert scale (from 1 – ‘Never’ or ‘Almost Never’ to 6 – ‘All of the time’). The Hungarian adaptation of the YSI was applied in previous studies (Salgó et al, 2021 ; Szalai, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Answers are rated on a 6-point Likert scale (from 1 – ‘Never’ or ‘Almost Never’ to 6 – ‘All of the time’). The Hungarian adaptation of the YSI was applied in previous studies (Salgó et al, 2021 ; Szalai, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Schema modes are organized into four categories: child modes, coping modes, parent modes, and the Healthy Adult mode. Modes can be adaptive (the Healthy Adult and the Happy Child mode) or maladaptive (every other mode) (for a short description of schema modes, see Table 1) (Salgó, Bajzát, & Unoka, 2021;Young, Klosko, & Weishaar, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of schema therapy in mitigating externalizing behaviors could be justified by the fact that the traits of individuals with externalizing behaviors are associated with their distorted understanding of the world and a perceived unfair environment. This cognitive factor contributes to the emergence of disruptive behaviors (15). Researchers have also demonstrated a correlation between perceived unfairness and anger with other negative outcomes (26,27).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, it seems that a change in a 'deeper mode' is more effective and stable. Modes form more complex mechanisms such as somatic reactions, thoughts, feelings, and behaviors, thereby leading to a more global and stable change (15). In ST-CA, the mode model is primarily employed as it enables the use of a simpler language and more therapeutic diversity.…”
Section: Internalizing and Externalizing Behaviors Often Emerge During Adolescence And Early Interventions Couldmentioning
confidence: 99%
“…Hemmati Sabet et al (20) demonstrated that employing cognitive therapy techniques helped patients learn to argue against incompatible perfectionism schemas and question their validity on a logical level. Furthermore, research findings suggest that the schema-based approach is effective for emotion regulation (21,22).…”
Section: Introductionmentioning
confidence: 98%